Optimization of the Drying Temperature for High Quality Dried Melissa officinalis - Xylia, Panayiota; Chrysargyris, Antonios (My University, 2025)
The drying temperature is one of the main factors affecting the storage of medicinal and aromatic plants (MAPs). The present study aimed to investigate the impact of different drying temperatures (20, 35, 42, and 49 °C) on Mentha officinalis quality attributes (moisture content, color, chlorophyll content) and the composition of its essential oil (EO), as well as the environmental impact, to determine the optimum drying temperature for this herb. According to the current findings, higher temperatures resulted in shorter drying times. However, this was accompanied by increased energy consumption and higher carbon footprint per hour of operation. Both room temperature (20 °C) and high oven temperature (49 °C) led to a darker colored product (i.e., higher browning index). Drying at 20 °C resulted in a higher EO yield compared to drying at higher temperatures (42 and 49 °C). Furthermore, lower temperatures (20 and 35 °C) and the highest temperature (49 °C) significantly decreased the levels of the two major EO compounds (geranial and neral), whereas both compounds were found in higher levels when the plants were dried at 42 °C. On the other hand, plants dried at 42 °C appeared to have the lowest amount of citronellal, significantly lower than those dried at the other tested temperatures. The results suggest that the optimum temperature for drying M. officinalis is at 42 °C, as it maintained the quality attributes of the dried product while also resulting in high quality EO.
Keywords: drying process; energy consumption; environmental impact; essential oil; lemon balm